Analisi Kerugian Akibat Wanprestasi Dalam Kontrak Bisnis Kendaraan Bermotor - Muhammad Abi Febriansyah; Zainudin Hasan; Ryan Justicia; Edi Prayitno (Peneliti.net, 2023)
Agreement by the parties as a basis for the legal relationship of the agreements that have been approved, which give rise to rights and obligations of the parties. With the expected agreement all of what has been agreed to function normally, but in practice in certain circumstances the exchange of achievement does not always work as it should so that it appears what is called a default. Default is: